Implementation of High Altitude Platform System in Development of National Defense Telecommunication Technology - Martharaharja, Januar Arief (International Journal of Psychosocial Rehabilitation, 2020)
This article will explain the concept of implementing High Altitude Platforms (HAPS) as the Main Backbone of military telecommunications in Indonesia. In the scientific map, this study is mainly included in defense science and defense technology in minor contexts which are within the scope of the field of sensing study in the sub field of remote sensing. This research uses exploratory research methods with a qualitative approach. Research data were collected using literature studies and analyzed with qualitative techniques consisting of three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study explain the factors of information security, signaling, regulatory requirements, topology, and cost factors needed to implement HAPs in the military realm to enhance national defense.